Antidepressant-like activity of ethanol extract of leaves of Caesalpinia pulcherrima in unstressed and stressed mice - Dinesh Dhingra; Deepak (Universidade de São Paulo, 2021)
In the present study, antidepressant-like activity of ethanol extract of leaves of Caesalpinia pulcherrima was evaluated in Swiss young male albino mice. Stress was induced in mice by subjecting them to unpredictable mild stress for 21 successive days. Ethanol extract of the leaves (100, 200 and 400 mg/ kg, p.o.) and fluoxetine (20 mg/kg, p.o.) were administered for 21 consecutive days to separate groups of unstressed and stressed mice. Ethanol extract (200 and 400 mg/kg) and fluoxetine significantly decreased immobility period of unstressed as well as stressed mice in tail suspension test (TST). However, the lowest dose (100 mg/kg) of the extract also significantly decreased immobility period of stressed mice in TST. The extract significantly restored reduced sucrose preference in stressed mice. There was no significant effect on locomotor activity of mice. Ethanol extract of the leaves significantly decreased plasma nitrite and corticosterone levels; brain MAO-A activity and MDA level; and increased brain reduced glutathione and catalase activity in unstressed as well as stressed mice as compared to their respective vehicle treated controls. Thus, ethanol extract of leaves of Caesalpinia pulcherrima showed significant antidepressant-like activity in unstressed and stressed mice probably through inhibition of brain MAO-Aactivity, reduction of oxidative stress and plasma corticosterone levels.